Geomechanical risk management and control at Andes Norte project: El Teniente mine - Landeros Córdova, P (Caving 2022: Proceedings of the Fifth International Conference on Block and Sublevel Caving, 2022)
El Teniente mine expansion plans are currently under development with construction stages through an integrated project strategy that will allow the continuity of future mining. The deepest sector corresponds to Andes Norte project, which has the additional mission of producing new knowledge and experience in deep mining. The project is planned as conventional panel caving with the application of hydraulic fracturing to mitigate the seismic hazard during future mining. It also considers the construction of the definitive material handling system, consisting of a crushing chamber with a capacity of 60,000 tons per day and a 9 km long tunnel to shelter the conveyor belt. This tunnel is currently under construction and the most complex zones have experienced rockbursts. This article describes the main elements that integrate the geomechanical risk management and control strategy for the Andes Norte Project, addressing risk concepts and strategies, mine design layouts, rock support design and hydraulic fracturing considerations, in addition to the experience gained during its construction and also with El Teniente mine experience applied to this future mining sector.
Keywords: risk management